(ﺗﻘوﯾم ﻛﺗب ﻓﻘﮫ اﻟﻠﻐﺔ(ﺑﺣث ﻣﺳﺗل ﻣن اطروﺣﺔ دﻛﺗوراه (Journal of the College of Education for Women, 2019)
This work was conclud by an appreciation of Fikh al-Logha books by objective critics raising from the idea of determining Fikh al-Logha terms and to appreciate modern offerts. The important issue in appreciation was the originality and dependency because all Fikh al-Logha books are based on the concept of originality and dependency.